Islamic Economic Approach to the Decision to Become a Customer: The Mediating Role of Interest in the Influence of Business Capital, Sharia Services, and Islamic Financial Knowledge - Seftiana, Erika; Junaidi, Heri; Anwar, Deky (Jurnal Iqtisaduna, 2025)
This study aims to obtain empirical evidence regarding the effect of business capital, service quality, and knowledge on the decision to become a customer with interest as a mediating variable at PT PNM Mekaar Syariah Kertapati District Palembang. The quantitative approach with SmartPLS-4 is based on Theory of Planned Behavior and needs theory. The results show that business capital and service quality significantly directly affect the decision to become a customer, while knowledge does not. Interest significantly affects the decision to become a customer and is mediated by business capital and expertise, but not by service quality. In addition, venture capital and knowledge significantly affect interest, while service quality does not. These findings confirm the importance of venture capital and Sharia literacy in influencing customer interest and decisions in Islamic microfinance institutions.